How integrative taxonomy can save a species from extinction: The supposedly extinct mouse opossum Cryptonanus ignitus (Diaz, Flores and Barquez, 2000) is a synonym of the living C. chacoensis (Tate, 1931) (2019)
We reviewed the taxonomic status of the “extinct” mouse opossum Cryptonanus ignitus (Diaz, Flores and Barquez, 2000). This species is only known from the type, an adult male collected in the province of Jujuy, northwestern Argentina, in 1962. Based on both qualitative and quantitative external and cranial traits and the analysis of DNA sequences extracted from the 57-year-old type skin, we confirm the suggestion of previous researchers that C. ignitus is an elderly example of the living species C. chacoensis (Tate, 1931). Most of the supposedly diagnostic morphological traits of C. ignitus (e.g., zygomatic arches unusually wide and robust, postorbital process of the jugal massively developed, prominent temporal scars) are age-correlated in didelphids and were observed in other adult specimens of C. chacoensis. The clay coloration of the ventral pelage of C. ignitus, which allegedly sets apart this species from other congeners, is here reported for new examples of C. chacoensis from other localities. Our results suggest the need to carefully evaluate the taxonomic status of other species supposed to have become extinct in recent times in mainland South America. © 2019 Deutsche Gesellschaft für Säugetierkunde